Neutrophil Expression of T and B Immunomodulatory Molecules in HIV Infection - Márquez-Coello, Mercedes; Ruiz-Sánchez, Cristina; Martín-Aspas, Andrés; Fernández Gutiérrez Del Álamo, Clotilde; Illanes-Álvarez, Francisco; Cuesta-Sancho, Sara; Girón-González, José-Antonio (Frontiers in Immunology, 2021)
Objective. Evaluate the expression of B and T cell immunomodulatory molecules in polymorphonuclear neutrophils (PMN) in HIV-infected patients. Methods. HIV load, bacterial translocation and neutrophils' expression of T [programmed death ligand, interleukin-10+, arginase 1+] and B [BAFF, APRIL] molecules were analyzed in different cohorts and time points: a control group of 25 healthy individuals and two groups of HIV-infected patients. Group 1 of patients included 35 untreated patients, studied at baseline and after antiretroviral therapy (ART). Group 2 was composed of 25 patients with undetectable viral load after a median of 101 months of ART prior to inclusion in the study. Results. Compared with the control group, group 1 patients showed increased bacterial translocation and their PMN had a significantly higher expression of T and B-cell immunomodulatory molecules, both at baseline and after 12 months of ART. Group 2 patients showed reduced bacterial translocation levels when compared with group 1 patients after 12 months of treatment. PMN expression of B-cell modulators was similar between group 2 patients and healthy controls, although the expression of T-cell modulators remained increased. Conclusion. In HIV-infected patients, the expression of B-cell stimulatory and T-cell suppressive molecules by neutrophils was increased at baseline and after a limited time of therapy. After a prolonged period of ART, only PMNs expression of T-cell immunosuppressive molecules remained elevated. These findings suggest the influence of bacterial translocation on B and T cell immunomodulatory role of PMNs.